Isolation of glutamic acid-producing lactic acid bacteria and its application in thosai. - Zareian, Mohsen (2011)
n the present study, six different fermented foods were evaluated as potential source for the isolation and characterization of glutamic acid-producing lactic acid bacteria. A total of two hundred and seventy isolates were screened sequentially for catalase activity and Gram-staining, out of which, 218 were categorized as lactic acid bacteria (LAB). Microscopic and biochemical tests were used to further identify and authenticate these 218 presumptive LAB strains. The results of the HPLC analysis revealed that only 35strains,out of 218, have glutamic acid producing ability. The highest glutamic acid production potential was exhibited by the strain TMP 3b85, isolated from tempeh (fermented soybean). Further tests involving the use of 16S rRNA gene sequencing and sugar assimilation assay identified TMP 3b85 as Lactobacillus plantarum.Time-course analysis of the culture medium revealed the glutamic acid production ability of TMP 3b85 to be maximumafter 96 h. In addition, characteristics of L.plantarumsuch as growth rate, glucose consumption and pH profile affecting the yield of glutamic acid during fermentation were alsoevaluated.The fermentation process parameters such as pH, temperature, carbon source (glucose) and nitrogen source (ammonium nitrate) were optimized through factorial design and Response Surface Methodology to obtain the highest yield of glutamic acid in a basal medium. The highest glutamic acid level (3.353 mM) was obtained under the following optimized conditions: pH, 4.5; temperature, 37 °C; glucose, 12%; ammonium nitrate, 0.7%. In order to investigate glutamic acid production by L.plantarumin a food system, thosai was chosen as a substrate. L.plantarum (4.36 x 107 CFU/ml) was inoculated into the fermentor containing thosai ingredients including29.7 g rice; 45 g wheatflour and 9.9 g skim milk powder in 84.6 ml distilled water. Fermentation was performed at ambient room temperature (29 °C); agitation rate 150 rpm for 216 h. Highest yield of glutamic acid was obtained (277 mg/kg) after 120 h. The findings of this study provide a potential basis for exploiting selected fermented food-related LAB as an alternative source for production of glutamic acid as a precursor of γ-amino butyric acid.